Effect of Different Factors on the Quality of Life and Sequelae of COVID-19 Patients After Discharge - Haijuan Wang; Nan Guo; Ya-Ping Yao; Le Song; Guan-Zhen Wang; Jun-Li He; Ning Zheng; Qiong Mo; Wen-Xu Ni; Bo Zhang; Fu-Sheng Wang; Lei Huang (​​​​​​​​Infectious Diseases & Immunity)
Abstract. Background. The continued spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) remains an international public health emergency, resulting in a significant global disease burden. The long-term effects of SARS-CoV-2 infection in humans and the long-term prognosis of patients with coronavirus disease 2019 (COVID-19) after discharge remain unclear. We aimed to assess the quality of life (QoL) and sequelae in patients with COVID-19 after discharge from the hospital by conducting multiple follow-up visits to understand the long-term effects of SARS-CoV-2 on patients' health and its possible influencing factors. Methods. COVID-19 patients discharged from Huoshenshan Hospital (Wuhan, China) between February 15 and April 5, 2020, were followed up at 6, 9, and 12 months after discharge. They completed questionnaires on postdischarge QoL and sequelae under the guidance of medical staff with professional training. The demographic and clinical characteristics of the COVID-19 patients were analyzed using descriptive statistics. A generalized estimating equation model was used to analyze the QoL-related factors. The χ2 test (or Fisher exact test) and multivariate logistic regression analysis were used to analyze the sequelae and influencing factors. Results. A total of 175 patients participated in at least 1 follow-up visit, and 120 completed all 3 follow-up visits. Patients diagnosed with severe and critically ill COVID-19 had worse mental conditions (χ2 = 7.653, P = 0.022) than those with the nonsevere type (not severe or critical) and were more likely to feel fatigued (χ2 = 4.836, P = 0.028). Female patients had a higher risk of sleep disturbance (χ2 = 10.026, P = 0.002) and dyspnea (χ2 = 5.672, P = 0.017) and had more difficulty returning to their original work and life (χ2 = 8.922, P = 0.003) than male patients. Patients with diabetes had a worse appetite (χ2 = 4.669, P = 0.031) and were more prone to sleep disturbance (χ2 = 4.417, P = 0.036) after discharge. The proportion of patients with at least 1 sequela increased from 29.76% (50/168) at 6 months to 51.11% (69/135) at 9 months (χ2 = 14.305, P < 0.001). Compared with the nonsevere type, patients diagnosed with severe and critically ill COVID-19 had an odds ratio (OR) of 4.325 (95% confidence interval [CI], 1.215–15.401) for memory decline. Female patients had an OR of 4.632 (95% CI, 1.716–12.501) for joint or muscle pain. Patients with hypertension had an OR of 3.014 (95% CI, 1.193–7.615) for joint or muscle pain. Conclusion. One year after discharge, there were still some patients with varying degrees of decline in QoL and sequelae, which occurred in all follow-up visits. Moreover, QoL and sequelae after discharge were related to sex, clinical classification of COVID-19, and underlying diseases.